PRESERVING TRADITIONAL CULINARY OF SEMARANG AND ITS DISTRICT AS CULTURAL HERITAGE TO SUPPORT CENTRAL JAVA TOURISM PROGRAM TROUGH MULTIMEDIA - Wienny Ardriyati; Julius Arya Wiwaha; Budi Hartono (Universitas Stikubank (UNISBANK) Semarang, 2014)
The specific objective of this study is to know the diversity of traditional snacks, especially in Semarang and its districts which have uniqueness in terms of its making and flavors. It is qualitative descriptive study, the technique of collecting data is through observation on the type of traditional snacks, interviewing the vendors who makes and sells the snacks in the traditional market, recording the process of making products in the form of photo and videos. The findings show twelve typical traditional culinary as cultural heritage that need preserving and documenting with multimedia so as to be known for the future generation and also help to promote for tourism. Keywords: culinary, traditional snack, multimedia